Comunicazione aziendale e sostenibilità: uno sguardo critico sul green advertising - Provenzi, Luna (Cambio (Firenze), 2025)
Green advertising promotes products and services using pro-environmental claims that present for-profit organizations as concerned about environment problems. This article presents evidence from a sociological investigation on the Italian market, based on a sample of 35 commercial advertisements dealing with environmental sustainability, which have been analyzed through Multimodal Critical Discourse Analysis (MCDA). The goal of the research is threefold: 1) to pinpoint the features of green ads discourses; 2) to illustrate their role in building the reputation of for-profit organizations; 3) to identify connections with the dominant ideas of consumption, nature and environment issues. While the representation of specialists and data make discourses sound trustworthy, storytelling and language appear incomplete, ambiguous and construable. Since MCDA focuses only on visual and linguistic categories, I propose new thematic ones, such as man-nature relationship and consumption role, in order to make the analysis more systematic and its results easier to compare.